Translation didactics: A proposal for teaching consecutive interpreting - Woodward-Smith, Elizabeth; Lankiewicz, Hadrian A.; Szczepaniak-Kozak, Anna (Glottodidactica, 2018)
The current article presents an example of a consecutive interpreting activity, which draws on the concept of autonomy in language learning. With regard to the "applied" component of translation studies, as formulated by Holmes (1988), the authors intend to demonstrate the need for enhancing foreign language competence in translator education, accentuating its role in the conceptualization of the discipline. Considering the context of this type of education, which is offered frequently to undergraduate students, the authors posit the need to concomitantly develop the command of a foreign language. They propose to compensate teaching practices derived from translation studies with the use of foreign language methodology for developing translating and interpreting skills.